The Effect of Bridging Exercise on Muscle Strength and Body Balance in Stroke Patients at National Brain Center Hospital Prof. DR. Mahar Mardjono East Jakarta - Desvita, Eva; Sofiani, Yani; Yunitri, Ninik (STIKep PPNI Jawa Barat, 2024)
Aims: The study aimed to determine the effect of bridging exercise on muscle strength and body balance in stroke patients at national brain center hospital Prof. DR. Mahar Mardjono East Jakarta. Methods: This study used experimental design aimed to test the application of bridging exercise to body balance and muscle strength in stroke patients. This study was conducted in one group with pre and post-test design. This study was conducted at National Brain Center hospital Prof. DR. Mahar Mardjono East Jakarta. The bridging exercise was conducted at 2-weeks, with light tp moderate intensity, three times a week, with 30 to 45 minutes every session. Results: The result of the statistical test with the Paired Samples t-Test P value resulted in 0.001. These result mean that bridging exercise has a significant effect on muscle strength in stroke patients with a mean difference of -0.63 (CI: -0.91-0.34) and a significantly improved the balance of patients with a mean difference of 17 (CI 12.1-21.9) and a high magnitude of effect (1.69). Conclusion: These result mean that bridging exercise has a significant effect on muscle strength in stroke patients.